Canada's response to invasion by Asian longhorned beetle (Coleoptera: Cerambycidae) in Ontario. Issue 1 (26th April 2022) - Turgeon, J.J.; Gasman, B.; Smith, M.T.; Pedlar, J.H.; Orr, M.; Fournier, R.E.; Doyle, J.; Ric, J.; Scarr, T.
Abstract: A reproductive population of the Asian longhorned beetle, Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae), an adventive insect from Asia, was discovered in 2003 in an urban landscape in Ontario, Canada. This polyphagous beetle, which attacks maples, Acer spp. (Sapindaceae), had the potential to seriously and permanently alter the composition and structure of forests in eastern North America. The Canadian Food Inspection Agency (CFIA) developed and implemented an eradication programme, with partners from various agencies in both Canada and the United States of America. Surveys were used to delineate the infestation and establish a regulated area around it. Treatment consisted of removing and destroying both trees with signs of A. glabripennis injury and trees assumed at high risk of being injured within the regulated area. After nine years of monitoring the regulated area, the CFIA declared A. glabripennis eradicated on 5 April 2013. Herein, we detail the response undertaken, summarise lessons learned, and provide preliminary observations and results pertaining to the arrival, establishment, and spread of A. glabripennis in Ontario.